Comparative studies on coating materials of urotropine modified furfurylolated-tCNSL and methylolated-tCNSL thermoset for anticorrosive application: Switching towards a cleaner approach. (15th April 2022) - Masood, Shumaila; Ghosal, Anujit; Gupta, Anjali; Zafar, Fahmina; Kumari, Reena; Alam, Manawwer; Nishat, Nahid
Abstract: Urotropine (UT, 5–25 wt%) modified furfurylolated and methylolated technical Cashew Nut-Shell Liquid (tCNSL-Fur-UT, and tCNSL-Met-UT) were prepared to study the potential of greener derivatives as polymeric alternatives to petroleum products. Resins were synthesized using condensation reaction, green reactants (tCNSL, & furfural), and UT as a crosslinker. The chemical structures along with change in participating functional groups (-OH, –C=O, –NH) were established by Fourier Transform Infra-Red (FTIR) and Attenuated Total Reflectance (ATR) spectral analysis. Glass transition (Tg ) and molecular changes with temperature was investigated by Differential Scanning Calorimetry (DSC). The coatings were studied for their potential to resist various corrosive chemicals (3.5% acid, 3.5% alkali, 3.5% saline and water). Thermal properties were investigated using Thermogravimetric Analysis (TGA), Differential TGA (DTG) (N2 environment), and heating in an oven. The high thermal stability of the resin (>400 °C) supports the formation of well crosslinked and stable polymeric system. Systematic "American Society for Testing and Materials" (ASTM) analysis reveals the hydrophobic (107°), flexible, glossy (98 GU) and resistance to scratch, impact as well as bending abilities of formulated films. Electrochemical Impedance Spectroscopy (EIS) studies revealed superior corrosion inhibition ability (>90%) even after 40 days of constant exposure to corrosive (NaCl solution) ions. The tCNSL-Fur-UT15 was found to have superior properties among other systems, projecting 15% UT as the optimum crosslinker. The study highlights the importance of cleaner production of materials through tCNSL (Agro waste), zero residues, and green chemistry principles. It gives a perspective of broadening the scope of tCNSL as thermally stable and mechanically robust polymeric substitute to petroleum derivatives in practical anticorrosive applications. Graphical abstract: Image 1 Highlights: tCNSL (renewable resource) based benzoxazine thermosets were prepared using acid catalyst. Comparative studies of urotropine modified tCNSL-Furfuraldehyde/Formaldehyde based benzoxazine resins were carried out. tCNSL-Fur-UT have better corrosion inhibition efficiency (90%) up to 40 days along with excellent thermal and chemical properties. tCNSL-Fur based coatings contribute well towards cleaner environment under the part of an efficient industrial waste management and utilization of green chemistry principles.